2014
DOI: 10.1007/s11524-014-9909-0
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Environment and Urban African American Marijuana Use during High School

Abstract: African American male high school students have the highest rates of marijuana use among all racial, ethnic, and gender groups, yet there is limited research examining contextual factors salient to the African American community. The purpose of this study was to examine how neighborhood environment measured in 8th grade is related to longitudinal transitions in marijuana use during high school (9th to 12th grades) in a sample of urban African Americans. Four hundred and fifty-two African American children were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 33 publications
(41 reference statements)
4
21
0
Order By: Relevance
“…Part of the explanation may lie in the widening income gap between white and black and Hispanic individuals during 71 and after 72 the 2008 recession, possibly leading to increased minority stress and demoralization and substance use as a coping mechanism. 7375 Increasing economic disparity of black and Hispanic individuals relative to white individuals may also have exacerbated neighborhood environmental factors (neighborhood disorder, violence, and visible drug sales) that increase the risk for adolescent marijuana use 75 and may also apply to adults. Compared with white individuals, minorities may also hold different attitudes toward marijuana (eg, viewing marijuana positively as a “natural” product 76 ) also warranting investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Part of the explanation may lie in the widening income gap between white and black and Hispanic individuals during 71 and after 72 the 2008 recession, possibly leading to increased minority stress and demoralization and substance use as a coping mechanism. 7375 Increasing economic disparity of black and Hispanic individuals relative to white individuals may also have exacerbated neighborhood environmental factors (neighborhood disorder, violence, and visible drug sales) that increase the risk for adolescent marijuana use 75 and may also apply to adults. Compared with white individuals, minorities may also hold different attitudes toward marijuana (eg, viewing marijuana positively as a “natural” product 76 ) also warranting investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with notable increases in the prevalence of cannabis use and cannabis use disorders among blacks (29, 53–55). While reasons for this change are unclear, increasing economic disparity between blacks and whites since the 2008 economic recession (56, 57) may have exacerbated neighborhood factors (disorder, violence, visible drug dealing) that increase adolescent marijuana use (58), and may function similarly in adults, an issue warranting investigation. Blacks may also hold different attitudes towards marijuana than whites, possibly viewing it as a natural and therefore safe substance (22).…”
Section: Discussionmentioning
confidence: 99%
“…In a sample of primarily Black youth in Baltimore, neighborhood physical, but not social disorder, was associated with marijuana use after high school (Furr-Holden et al, 2011, 2014). Using data from the same study but restricted to Blacks, Reboussin et al (2014) found that perceptions of neighborhood disorder, increased drug activity and exposure to violence in 8 th grade were associated with initiation and progression to more frequent marijuana use between 9 th and 12 th grades.…”
Section: Introductionmentioning
confidence: 99%